Sistem Informasi Tanggap Darurat Bencana Banjir Lhoksukon Menggunakan Aplikasi Android Berbasis IoT - Amrullah, Muhammad Halim, Syahrul Ramadhan, Yuswandi (Jurnal Elektronika dan Teknologi Informasi, 2023)
Floods occur almost every year for residents close to the capital city of North Aceh and floods are also caused by the overflow of the Lhoksukon river. This research implements an information system that will provide information to the community in real-time that a flood disaster will soon occur due to the overflow of the Lhoksukon river, so that the community can immediately be alert and anticipate. The system is built based on Android and IoT.